Conjugated Linoleic Acid and Brain Metabolism: A Possible Anti-Neuroinflammatory Role Mediated by PPARα Activation - Murru, Elisabetta; Carta, Gianfranca; Manca, Claudia; Sogos, Valeria; Pistis, Marco; Melis, Miriam; Banni, Sebastiano (Frontiers in Pharmacology, 2021)
Fatty acids play a crucial role in the brain as specific receptor ligands and as precursors of bioactive metabolites. Conjugated linoleic acid (CLA), a group of positional and geometric isomers of linoleic acid (LA, 18:2 n-6) present in meat and dairy products of ruminants and synthesized endogenously in non-ruminants and humans, has been shown to possess different nutritional properties associated with health benefits. Its ability to bind to peroxisome proliferator-activated receptors (PPAR) α, a nuclear receptor key regulator of fatty acid metabolism and inflammatory responses, partly mediates these beneficial effects. CLA is incorporated and metabolized into brain tissue where induces the biosynthesis of endogenous PPARα ligands palmitoylethanolamide (PEA) and oleoylethanolamide (OEA), likely through a positive feedback mechanism where PPARα activation sustains its own cellular effects through ligand biosynthesis. In addition to PPARα, PEA and OEA may as well bind to other receptors such as TRPV1, further extending CLA own anti-neuroinflammatory actions. Future studies are needed to investigate whether dietary CLA may exert anti-inflammatory activity, particularly in the setting of neurodegenerative diseases and neuropsychiatric disorders with a neuroinflammatory basis.